Superconvergences of the Adini's Element for Second Order Equation (Journal of Computational Mathematics, 2021)
In this paper, the asymptotic error expansions of Adini's element for the second order inhomogeneous Neumann problem are given and the superconvergence estimations are obtained. Moreover, a numerical example to support our theoretical analysis is reported.